2023
DOI: 10.1080/0886022x.2022.2163904
|View full text |Cite
|
Sign up to set email alerts
|

The body mass index change is associated with death or hemodialysis transfer in Japanese patients initiating peritoneal dialysis

Abstract: A decreased body mass index (BMI) over time is associated with a poor prognosis for patients on hemodialysis. We aimed to examine whether this association also applies to patients with peritoneal dialysis (PD). BMI change was defined as the percentage change in the BMI between the time of PD catheter insertion and six months after its insertion. The association between the BMI change and all-cause mortality or PD discontinuation from six months after PD catheter insertion until October 2021 was investigated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Of note, in the current study, after adjusting for BMI trajectory in the Cox hazard analyses, the relationships between TSF, MUAC trajectories, and all-cause mortality were still observed. Although previous studies have proven that a declining body weight, commonly defined with BMI or WC, is associated with higher mortality 34 , 35 , some studies demonstrated that BMI and its change were not associated with mortality 36 , 37 . Taken the accuracy of BMI trajectory could be influenced by a change in body water balance, BMI might diminish the reproducibility of this measure, weakening the association with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in the current study, after adjusting for BMI trajectory in the Cox hazard analyses, the relationships between TSF, MUAC trajectories, and all-cause mortality were still observed. Although previous studies have proven that a declining body weight, commonly defined with BMI or WC, is associated with higher mortality 34 , 35 , some studies demonstrated that BMI and its change were not associated with mortality 36 , 37 . Taken the accuracy of BMI trajectory could be influenced by a change in body water balance, BMI might diminish the reproducibility of this measure, weakening the association with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In the longitudinal study, demographic data, including age, sex, DM status, and CCI, as well as the use of antihypertensive drugs or diuretics, were collected at the time of PD initiation. Additionally, BP levels, as well as anthropometric and biochemical data including BMI, serum albumin levels (mg/dL), an estimated glomerular filtration rate calculated from serum creatinine using three-variable Japanese equations [9], C-reactive protein (CRP) levels (mg/dL), brain natriuretic peptide (BNP) levels (pg/mL) and a geriatric nutritional risk index (GNRI) calculated from BMI and serum albumin levels, were collected at the time of PD initiation and 6 months later, as previously described [8], in addition to the serum urea-to-creatinine ratio. Furthermore, the dialysis/plasma creatinine ratio at 4 h (D/P4) was determined using a standard peritoneal permeability test (PET) within 6 months of PD catheter insertion.…”
Section: Data Collection and Patient Evaluationmentioning
confidence: 99%